Sistem Informasi Musyawarah Perencanaan Pembangunan (Musrenbang) Kabupaten Studi Kasus Pada Badan Perencanaan Pembangunan Daerah (Bappeda) Kabupaten Pati - Iman Ardhi Prabowo; Fajar Nugraha (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2018)
Deliberation planning development (Musrenbang) district or city is a deliberation of stakeholders at the district / municipal level to finalize the draft regional government work plan (RKPD) district or city. The regency Musrenbang organizer is the district or city Bappeda. Beginning with the establishment of the Musrenbang Observer Team (Kepanitiaan) by the Head of the District / Municipal Bappeda by involving all the heads of the field in Bappeda. The purpose of this research is to build Information System Musrenbang Development Planning (Musrenbang) Pati District which is used for the management of development planning by Bappeda and the Working Unit. System development method used is System Development Life Cycle. The design of information systems using Data Flow Diagrams (DFD) used to describe information systems development planning consultation (Musrenbang) district at the regional development planning agency (bappeda) Pati district.Keywords: Information Systems; Musrembang; Data Flow Diagram.